The annual cycle of spermatozoa content in the vas deferens and some reproductive parameters in the narrow-clawed crayfish Pontastacus leptodactylus (Eschscholtz, 1823) - Farhadi, Ardavan; Harlioglu, Muzaffer Mustafa (Elsevier, 2019)
Understanding the annual dynamic of gametes in crayfish is useful for successful management of crayfish population. The annual variations in spermatozoa content of vas deferens, gonado-somatic index (GSI), hepatosomatic index (HSI), vas deferens index (VDI), and testicular index (TI) were investigated in male Pontastacus leptodactylus. The spermatozoa content, GSI, HSI, VDI, and TI of P. leptodactylus significantly (P < 0.05) changed during different seasons of the year. For example, significantly higher spermatozoa number, GSI, VDI, and TI were recorded in January (P < 0.05). On the other hand, the HSI reached the peak in August (P < 0.05). The spermatophore degeneration started in April. Although the vas deferens lacks spermatophore structure during the summer, the presence of spermatozoa was observed throughout the year. This study represents a step forward in understanding the seasonal spermatozoa content and the reproductive status of male P. leptodactylus.
Keywords: Decapoda; Gonado-somatic index; Hepatosomatic index; Spermatophore; Vitellogenin